Core instability models of giant planet accretion and the planetary desert - Miguel, Yamila (2008)
With the aim of studying the final mass distribution of extrasolar planets, we have developed a simple model based on the core instability model, which allows us to form a large population of planets and make them evolve in circumstellar discs with various initial conditions. We investigate the consequences that different prescriptions for the solid and gas accretion rates would have on this distribution and found that it is strongly dependent on the adopted model for the gas accretion.